Impact of Phosphogypsum on Viability of Trichuris suis Eggs in Anaerobic Digestion of Swine Manure - Olexandra Boyko; Viktor Brygadyrenko; Yelizaveta Chernysh; Viktoriia Chubur; Hynek Roubík (Microorganisms)
Waste from livestock farms contains various pathogens, including eggs and larvae of helminths—pathogens of parasitic diseases harmful to animals and humans. One of the methods for their effective processing to obtain biofertilizer and biofuel is anaerobic digestion, which requires further improvement to completely suppress the viability of pathogenic microorganisms in mesophilic conditions. To this end, the use of anaerobic digestion under sulfate reduction conditions to suppress pathogens using biogenic hydrogen sulfide is promising. Consequently, this study aims to study the effect of a sulfur-containing additive such as phosphogypsum on the disinfection of pig manure during anaerobic digestion. Egg mortality was already found to increase significantly compared to the control (80% and more), even at a minimum concentration of phosphogypsum (5%), on the fifth day of the experiment. At the same time, the maximum effect (100% mortality of Trichuris suis eggs) was recorded at a 10% concentration of phosphogypsum, starting from the 10th day of the study. Our experiment showed that changes in anaerobic digestion conditions using phosphogypsum could positively affect digestate disinfection. However, further research is needed to optimize the conditions of the process for an effective combination of disinfection with the production of environmentally safe organic fertilizers and high-quality biogas with a high level of methane.